Technology-Supported Teacher Learning Communities for Sustainable Professional Development - Hartati, Sri; Lestari, Slamet (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
Teacher Learning Communities (TLCs) have increasingly evolved from conventional collaborative forums into technology-supported professional learning ecosystems that facilitate continuous teacher development in response to digital transformation in education. This study investigates the characteristics, research trends, and conceptual foundations of technology-supported TLCs through a systematic review integrated with bibliometric analysis. Publications indexed in the Scopus database were identified using the PRISMA framework. From 143 initial records, 94 peer-reviewed articles published between 1999 and 2025 met the inclusion criteria for bibliometric analysis, while 12 open-access studies were examined in depth to synthesize key conceptual findings. VOSviewer was employed to map publication trends, international collaboration, institutional affiliations, and keyword co-occurrence networks. The findings reveal that research on TLC has grown steadily, particularly after 2016, although scholarly contributions remain concentrated in a limited number of countries. More importantly, the analysis identifies six interconnected dimensions underpinning sustainable technology-supported professional development: professional collaboration, learning assessment and research methodology, sustained professional development, local context and cultural adaptation, technology innovation in learning, and effective leadership and institutional structure. Among these, technology innovation in learning functions as an enabling element that strengthens collaboration, reflective practice, knowledge sharing, and continuous professional learning. The study also highlights emerging themes, including pedagogical content knowledge, teacher mentoring, trust among members, reflection, democratic leadership, capacity building, and learning effectiveness, as promising directions for future research. These findings provide a conceptual foundation for designing technology-responsive teacher professional learning ecosystems that support sustainable instructional improvement.